The Influence of Spiritual Leadership on Innovative Work Behavior through Employee Interpersonal Justice - Asj’ari, Fachrudy; Alfa Rizki, Rayhan Ahmad; Andy Andreawan; Aristyanto, Erwan (International Journal of Economics, Commerce, and Management, 2025)
This research falls under the category of Human Resources, which includes planning, organizing, managing, and controlling individuals who are considered valuable assets by companies. The goal is to achieve the goals that the company has set. The focus of the research to be carried out is to test how spiritual leadership influences innovative work behavior, by paying attention to the role of employee interpersonal justice at PT. Multi Spunindo Jaya, Tbk which is located in Sidoarjo. The type is quantitative with data analysis techniques collected through statements in the form of questionnaires and analyzed using SEM_PLS techniques with the SmartPLS 4.0 tool. This population is 780 employees taken from PT. Multi Spunindo Jaya, Tbk in Sidoarjo. The sample in this study was taken from 62 employees through the Issac and Michael formula with purposive sampling technique. The research aims to analyze how spiritual leadership and interpersonal justice play a role in optimizing the innovative work behavior of employees of PT. Multi Spunindo Jaya, Tbk in Sidoarjo. This research is useful for developing knowledge about MSDM. The results of the research that has been conducted show that spiritual leadership and interpersonal justice have a significant and positive effect on innovative work bahevior, and also spiritual leadership has a significant and positive effect on interpersonal justice.